Peran kepercayaan dalam memediasi dampak konten afiliasi TikTok terhadap niat membeli secara digital - Marsa Azrani; Ratih Amelia (Universitas Widya Mataram, 2026)
The rise of artificial intelligence (AI)-generated affiliate content on TikTok raises an unanswered question: to what extent can such content build user trust and drive purchase intention. This study examines the role of AI-produced affiliate content on Generation Z's purchase intention, with trust as a mediating variable, focusing on the TikTok account @OctapoLab.AI. A total of 149 Generation Z TikTok users in Surabaya were selected through purposive sampling and analyzed using PLS-SEM with SmartPLS 3. All four hypotheses were supported: AI-produced affiliate content had a positive and significant effect on trust (β = 0.547; T = 6.270; p < 0.001); trust had a positive and significant effect on purchase intention (β = 0.498; T = 7.507; p < 0.001); AI-produced affiliate content also positively and significantly influenced purchase intention (β = 0.367; T = 4.050; p < 0.001); and trust partially mediated the relationship between the two (β = 0.272; T = 4.119; p < 0.001). These findings indicate that accurate and consistent information quality can build consumer trust in AI-produced affiliate content. Digital creators are encouraged to prioritize information quality when designing AI-based affiliate strategies.